PEMBERDAYAAN PADA IBU PKK RT. 03 RW. 01 DESA PAMOLOKAN TENTANG PENTINGNYA IMUNISASI DASAR LENGKAP PADA ANAK BALITA - zakiyah yasin; Nailiy Huzaimah; Iva Gamar Dian Pratiwi (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2019)
Tunggak Jati Hamlet is one of the hamlets in Pamolokan Village located in the district.Sumenep City, a hamlet that has a fairly dense population. Communities who in fact have secondary education certainly need better knowledge of Basic Immunization, through the Village PKK provided Posyandu with the hope that the children in Tunggak Jati hamlet will get Complete Basic Immunization, but over time, many Tunggak Jati Hamlet communities do not know the importance and benefits of Complete Basic Immunization, in addition to the lack of the closest form of Posyandu socialization to the public about the importance of complete basic immunization in children under five is also a problem in the provision of Complete Basic Immunization. With the counseling about the Importance of Providing Complete Basic Immunization in Toddlers, it is expected that posyandu participants can do a healthy lifestyle and other precautions that will occur to provide complete basic immunization to their toddlers. Through this counseling it is expected: Realization of public knowledge about the importance of providing complete basic immunization in toddlers at the Posyandu in Pamolokan village, Sumenep City District.. The creation of a healthy environment in Pamolokan Village, Sumenep City District.. The active role of community leaders and family members in participating in improving public health in their environment, especially regarding the Importance of Complete Basic Immunization in Toddlers at the Posyandu in Pamolokan Village, Kota Subdistrict.